Gambaran Penderita Tuberkulosis Paru yang Berobat Menggunakan DOTSdi Puskesmas Bahu Malalayang I Periode Januari-Desember 2012 - Sihotang, Ruth Haryanti; Lampus, Benny S.; Pandelaki, August J. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Lung Tuberculocis is one of public health problems in the world especially in developing countries including Indonesia. According to a WHO report in 2007, an increase which is quite high which found as many as 9.27 milion new casus (139 per 100.000) and mortality rate of 19.7 per 100.000 population. WHO recommended DOTS strategy (Directly Observed Treatment Short-Course) for lung Tuberculocis cope with minimum recovery target of 85%. This study has done research aims to reveal the Lung Tuberkulocis patients who seek treatment at the health center using DOTS in Bahu Malalayang I period January to December 2012. This study used a retrospective descritptive method with a population of as many as 58 patients. The results of the study in patients with Lung Tuberculocis scorer with male gender (56.90%), the age group 25-49 years (44.22%), BTA Sputum (+) (93.10%) and approximately (91.38%), did not have a history of co-morbidities. Study patients with new cases around (91.38%) and result of patients who recovered (91.38%), and the recovery rate with BTA (+) (94.23%). as well as sputum smear conversion (94.23%). Keywords : Characteristics of Patients with Lung Tuberculocis, Manado